2007
DOI: 10.1016/j.apmr.2007.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the State-of-the-Science in Rehabilitation Medicine and Its Implications for Medicare Postacute Care Policies

Abstract: Better measurement of the case-mix complexity of patients receiving rehabilitation services is critical to understanding variations in the outcomes achieved by patients treated in different postacute care (PAC) settings. The Medicare program recognized this issue and is undertaking a major initiative to develop a new patient-assessment instrument that would standardize case-mix measurement in inpatient rehabilitation facilities, long-term care hospitals, skilled nursing facilities, and home health agencies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…Gage et al 9 analyzed five diagnoses or procedure groups and found that half of these patients used more than one type of rehabilitation setting. DeJong et al 10 found that 92% of hip and knee arthroplasty patients continue to receive rehabilitation services after discharge from an SNF or an IRF.…”
Section: Examined Rehabilitation Activities In Snfs Andmentioning
confidence: 99%
“…Gage et al 9 analyzed five diagnoses or procedure groups and found that half of these patients used more than one type of rehabilitation setting. DeJong et al 10 found that 92% of hip and knee arthroplasty patients continue to receive rehabilitation services after discharge from an SNF or an IRF.…”
Section: Examined Rehabilitation Activities In Snfs Andmentioning
confidence: 99%
“…The change-in-functional-status data items added to the MDS came from the CARE Tool item set. Gage et al (2007) reported on the development of the CARE Tool, developed by CMS through a contract to RTI International to develop a PAC assessment tool for use in all PAC settings. The Post-Acute Care Payment Reform Demonstration tested the CARE Tool from 2008 to 2009 and finalized its development.…”
Section: Medicare Quality Reporting Programsmentioning
confidence: 99%
“…The Post-Acute Care Payment Reform Demonstration tested the CARE Tool from 2008 to 2009 and finalized its development. Although the CARE Tool has not been implemented in its entirety, Gage et al (2012) established its reliability.…”
Section: Medicare Quality Reporting Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the Centers for Medicare and Medicaid Services (CMS) Innovations Center has spearheaded the Partnership for Patients, testing innovative programs that will address the issues. For example, one initiative targets long‐stay dually eligible NH residents by contracting with seven organizations to assist 145 NHs with implementation of evidence‐based interventions and additional on‐site assistance to reduce unnecessary hospitalizations in this population . The 3‐day hospital requirement for SNF‐level care for individuals who meet specific clinical criteria may be modified in these new models.…”
mentioning
confidence: 99%